A Shift in The Politeness Actions of Grade 5 Elementary School Students With a Javanese Cultural Background : Pergeseran Tindak Kesantunan Peserta Didik Kelas 5 Dengan Berlatar Belakang Budaya Jawa - Mirmanto, Nurman; Prayitno, Harun Joko; Sutopo , Anam; Rahmawati, Laili Etika; Widyasari, Choiriyah (Universitas Muhammadiyah Sidoarjo, 2021)
The shift in the act of politeness directive set in Javanese culture in elementary school children began to shift and shift in a negative direction. This study aims: (1) to describe the form of shift in the act of politeness directive class 5 students in interacting with teachers with Javanese cultural backgrounds in elementary school. (2) To find out the factors that influence the shift in directive politeness acts towards teachers with Javanese cultural background. The approach used in this research is descriptive qualitative. Data collection using the Case study method: direct observation, listening and field records (Whaatsaap recording). Results of the study: 1) language politeness acts in grade 5 students of SDN Polokarto 01 in communicating and interacting with speech partners are still very low, a shift in politeness in language with a Javanese cultural background needs to be fostered or efforts to restrain the level of shift so as not to deviate too much from the upload .2.2) factors that make the shifting politeness act further include a) family, and parents. b) demographic factors in the surrounding environment. 3) strategic efforts to withstand the shift by reversing the existing cultural norms in society by prioritizing 1) Angon Rasa, 2) Adu Rasa. 3) Board 4) Humility 5) Respect 6) Salira tepa attitude.